Gender sensitivity in physical education classes in one state college - Ramonito N. Abesar (Northern Negros State College of Science and Technology (NONESCOST), 2023)
Gender sensitivity is a process by which individuals are made mindful of how sexual orientation plays a critical parcel in life through overseeing others. This study aims to determine gender sensitivity in a physical education class in one state college. It employs a descriptive type of research. The respondents are the Physical Education students taking up P.E.102 and P.E.224. In this study, the mean and t-test were used as statistical tools. Study shows that P.E. 102 (Rhythmic Activities) classes are female-dominated with a strong willingness to explore their talents and skills, while males have limited participation due to reservations. Moreover, P.E.224 (Team Sports) is male-dominated where males showed too much interest in ballgames, while females are reserved and less motivated. Females needed more time for training to master certain skills. Moreover, the study's results showed that there is no distinguishable difference in the degree of gender sensitivity in Physical Education Classes as perceived by the students when taken as a whole and when grouped according to sex. Therefore, it is recommended that teachers of Physical Education classes should develop a method that is the interactive type to increase gender sensitivity among students. The development of instructional intervention by the faculty and administration to increase awareness of gender issues should be encouraged as mandated.